Book Review: A Study of Diachronic Evolution of English and Chinese Causal Complex Sentences - Xie, Yajun (Pacific International Journal, 2025)
This paper presents a review of the monograph A Study of Diachronic Evolution of English and Chinese Causal Complex Sentences. It begins with an overview of the book's specific content, and then offers a comprehensive assessment focusing on aspects such as the research perspective, theoretical application, methodology, and typological value. The concluding section summarizes the book's academic contributions and application prospects, while also providing objective critical suggestions.